Gender, Race, and Precarity - Zuhra Abawi; Rachel Berman; Alana Powell (Atlantis)
This paper critically examines the parallels of devaluation encountered by early childhood educators and sessional faculty members in Ontario as reflective praxis. The three authors’ experiences are diverse and include a tenured professor and two sessional faculty members, both of whom have worked in the field of Early Childhood Education and Care (ECEC). The narratives of the authors inform the concerning trend of precarity and devaluation embedded within two polarizing spectrums of the Ontario educational landscape: Post-Secondary Education (PSE) and ECEC. Although these aforementioned areas of education rarely intersect, the authors centre them on the frontline of the neoliberal assault on education transpiring in Ontario today. The three authors self-identify as female settlers; two have doctoral degrees; one has an MA and is an early childhood educator (ECE). One author self-identifies as a racialized and white-coded cis-gendered woman, and two self-identify as white, cis-gendered women. All of the authors have worked in Ontario’s post-secondary landscape, one as sessional faculty member and then a tenured professor, and two as sessional faculty members. The paper will problematize the neoliberal assault on higher education and ECEC through a Feminist Political Economy (FPE) conceptual framework in order to draw on the multifaceted ways feminized discourses devalue the work of ECEs and perpetuate the overrepresentation of women, particularly racialized women in precarious faculty positions.